AB0744 Ocular involvement in giant cell arteritis: A cross-sectional study. (23rd January 2014) - Stagnaro, C.; Talarico, R.; Ferrari, C.; d'Ascanio, A.; Figus, M.; Bombardieri, S.
Abstract : Background: Giant cell arteritis (GCA) represents the most common primary vasculitis of the elderly, that usually involves large and medium sized arteries. Permanent partial or complete visual loss in one or both eyes is one of the most dreadful manifestations of GCA and has been observed in 15-20% of patients in most series. Objectives: The primary aim of the study was to evaluate the prevalence of impaired vision as first clinical symptom at the onset of disease, in a cohort of patients with GCA. The secondary aim was to compare the subset of patients characterised by the presence of ocular involvement with the others who didn't experience impaired vision Methods: The clinical charts of 220 GCA patients (176 females, mean ± SD age at the onset 70±7 years), all fulfilling the 1990 American College of Rheumatology criteria, were analysed. Prevalence of ocular involvement demonstrated by ophthalmological examination and/or visual field and/or fluorescein-angiography and/or optical coherence tomography were retrospectively analysed in all patients (pts). Results: Forty-three percent ( n =95) of pts presented at the onset of disease visual alterations. The most common presenting symptoms among pts who experienced ocular involvement were: visual loss (90%), amaurosis fugax (23%), diplopia (11%) and eye pain (3%). Anterior ischemic optic neuropathy was observed in 70% of the patients, while central retinal artery occlusion was revealed in 17% of cases. In all patients with permanent visual loss ( n =11), fundoscopic examination showed signs of ischemic optic neuropathy; moreover, among these, only 4 patients were affected by permanent bilateral visual loss. Any epidemiological or hematochemical difference was noted between patients who experience impaired vision and the others, except for the mean age at disease onset, that was higher in patients with ocular impairment (77±5 years). Conclusions: The wide spectrum of GCA clinical manifestations can extensively vary, from cranial symptoms, such as headache, jaw claudication or visual alterations, to constitutional symptoms. Impaired vision is often an early manifestation of the disease. Since risk of loss of vision after initiating glucocorticoids is very low, an early recognition and diagnosis is of primary importance. Disclosure of Interest: None Declared